The utilization of Whitney Rapids : from sawmill to paper company, 1831-1908 - Collar, William E. (My University, 1967)
The primary purpose of this work is to determine why the Nekoosa Paper Company was established at Nekoosa and to trace its history and development. To adequately cover the topic, it is necessary to follow the utilization of Whitney Rapids from the time the first sawmill was built until the paper company came into existence. A history of the enterprises preceeding the paper mill is essential for, had they been successful, the mill may never have been built., The success or failure of various businesses is explained, and some insight is given into the lives of the most significant entrepreneurs. The growth of the paper company from 1893 to 1908 is examined with a concentration on the building of the mill, its expansion, and the problems it encountered. An attempt is made to indicate how the mill affected the economy of the area and why it consolidated with other mills in 1908.
Keywords: Nekoosa -- Paper Company -- History; Paper industry -- Wisconsin -- Nekoosa; Nekoosa (Wis.) -- History; Lumbering -- Wisconsin -- Nekoosa